PENERAPAN METODE STAD DISERTAI MEDIA TORSO UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI - Saputra, Riska Agusrio; Santoso, Handoko (Bioedukasi Jurnal Pendidikan Biologi, 2013)
The results addressing the STAD method Torso with Media can improve biological activity and learning outcomes food Digestive System subject matter in class XI Science High School PGRI Bukitkemuning Academic Year 2012/2013. Student activity data on average in the first cycle by 63% in the second cycle obtained an average learning activity by 72% with an increase of 9% while for the learning outcomes of students has increased, the average initial score was 53.2 before PTK implemented , and at the end of the first cycle of 65.14, then on the second cycle of 72.28. To obtain an average yield improvement of student learning from cycle I to cycle II at 7.14%, even when compared with the prior PTK increased 35.86%. As for the suggestions to teachers fields of study, in order to study biological activities and results to achieve optimal results it is recommended to apply the methods of cooperative learning with media type STAD Torso by optimizing activities ask, discuss, do chores, and making observations.Â Key Words: STAD, learning activities, learning outcomes